Reversing complete mechanical transzonal projections disruption during mouse in vitro follicle culture with unaltered oocyte competence. Issue 6 (11th March 2021) - Herta, Anamaria-Cristina; Akin, Nazli; Billooye, Katy; Saucedo-Cuevas, Laura; Lolicato, Francesca; Segers, Ingrid; Anckaert, Ellen; Smitz, Johan
Abstract: In vitro oocyte growth is widely studied as an alternative fertility preservation approach. Several animal models are used to generate extensive information on this complex process regulated by the constant and dynamic interaction between the oocyte and its somatic compartment throughout follicle growth and maturation. A two-dimensional attachment mouse secondary follicle culture system was used to assess the oocyte's capacity to overcome disconnection from its somatic companions at different developmental stages for final competence acquisition. To test this, complete mechanical denudation of oocytes from preantral (PA) and early antral (EA) follicles was performed. Established endpoints were the oocyte's potential to reconnect with somatic cells and the impact of connectivity disruption on mature oocyte quality. This study proves that oocytes from PA and EA cultured mouse follicles can overcome complete denudation, restoring likely functional transzonal projections with no significant differences in meiotic and developmental competence compared with those from intact cultured follicles. These novel findings constitute good premises for developing successful strategies to rescue human oocyte competence in the context of in vitro culture approaches such as nonhuman chorionic gonadotropin triggered in vitro maturation. Abstract : Oocytes from preantral and early antral cultured mouse follicles restore likely functional transzonal projections with no significant differences in meiotic and developmental competence compared to oocytes from intact cultured follicles.